KONSELING MULTIDEMENSIONAL DALAM BIMBINGAN DAN KONSELING ISLAM : PENDEKATAN HOLISTIK DALAM MEMBANTU PERMASALAH KLIEN - Nadila Farahita; Fadila; Syamsul Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Multidimensional counseling is a counseling approach that views the individual holistically, encompassing physical, psychological, social, and spiritual aspects. In Islamic Guidance and Counseling, this approach is crucial because humans are viewed not only as biological and social beings but also as spiritual beings connected to Allah SWT. This study aims to examine the concept of multidimensional counseling from the perspective of Islamic Guidance and Counseling through a literature review. The method used was library research, analyzing various relevant journals and books. The results of the study indicate that multidimensional counseling in Islamic Guidance and Counseling is able to provide more comprehensive services because it considers all dimensions of an individual's life. This approach helps clients address psychological, social, and spiritual issues in a balanced manner, thereby achieving better mental health and well-being